ebXML 등록저장소를 이용한 이러닝 객체 메타데이터의 표현과 관리 - 김형도(Hyoung-Do Kim) (한국콘텐츠학회 논문지, 6(11), 2006)
E-learning objects should be appropriately described and classified using standard metadata for facilitating the processes of e-learning resource description, discovery and reuse. These metadata need to be published in a registry to reduce duplication of effort and enhance semantic interoperability. This paper describes how standard ebXML registries can be used for annotating, storing, discovering and retrieving e-learning object metadata. For semantic annotation of e-learning objects, IEEE LOM is adopted as the metadata ontology. In order to support the e-learning metadata ontology in interoperable ebXML registries, a mapping scheme between LOM and ebXML information model is proposed. The usefulness of standard ebXML registries for sharing e-learning metadata is demonstrated by prototyping an e-learning registry called ebRR4LOM based on the scheme. 이러닝 자원에 대한 재사용 과정을 편리하게 하기 위해서는 표준을 준수하는 메타데이터를 사용하여 이러닝 객체를 적정하게 기술하고 분류하는 작업이 필수적으로 요구된다. 이러한 메타데이터는 이러닝 객체의 재사용에 있어서 중복된 노력을 최소화하고 의미를 상호 이해할 수 있도록 등록저장소에 공개되는 것이 바람직하다. 본 논문은 이러닝 객체에 관한 메타데이터를 생성하고, 저장하고, 발견하며, 추출하는데 있어서 국제 표준인 ebXML(Electronic Business using extensible Markup Language) 등록저장소를 이용하는 방안을 제시한다. 국제적으로 광범위하게 채택되고 있는 IEEE LOM 표준을 준수하여 작성된 이러닝 객체 메타데이터를 ebXML 등록저장소에서 표현하고 관리할 수 있도록, LOM과 ebXML 정보모델간의 변환 체계를 제시하고, 이를 바탕으로 ebRR4LOM이라고 하는 이러닝 등록저장소 프로토 타입을 개발하여 이러한 등록저장소의 유용함을 설명한다.